The role of good corporate governance (GCG) and disclosure of corporate social responsibility (CSR) on financial performance in banking in indonesia - Yenni Vera Fibriyanti; Mohammad Syafik (Jurnal Ekonomi, 2024)
The financial performance of banks in Indonesia has fluctuated. One way to improve financial performance is through disclosure of corporate social responsibility (CSR). Corporate governance plays an important role in improving financial performance. This research aims to analyze the role of GCG and CSR disclosure on banking financial performance in Indonesia. This research takes secondary data on banking companies listed on the Indonesia Stock Exchange for the 2017-2022 period. In this research, researchers used a purposive sampling technique by setting certain criteria and obtained a sample of 41 banks or 240 research data. The data analysis technique used to solve problems in this survey is to use the Stata 12 program to carry out panel data regression analysis. The main finding in this research is that good corporate governance as proxied by independent commissioners and audit committees has no effect on financial performance, this may be due to a lack of optimal consideration in the appointment of independent commissioners and audit committees. Apart from that, it has been proven that CSR disclosure has a positive effect on financial performance. Social disclosure is considered capable of improving the company's image in the eyes of the public and attracting the attention of investors which will have an impact on the company's financial performance.